Schools Through the Perspective of Students from Different Countries: The Case of Spain, Italy, Poland, Portugal, Romania, and Turkey - Yurdagül Doğuş; Mehmet ÖZDOĞRU (Dinamika Ilmu, 2022)
This research was carried out to determine the perceptions of schools of students studying in five European Union countries (Spain, Italy, Poland, Portugal, Romania) and the candidate country Turkey. In the study, the data were obtained through the student opinion form created by the researchers and analyzed by content analysis. In the study, it was determined that most of the students had a positive perception towards the school and described the school with positive concepts, metaphors, emotions, and values. Students with a positive perception of school have described school with the concepts of learning, friendship, future, development, entertainment, life, responsibility; positive emotions such as success, happiness, trust, pleasure, interest, love, joy, and respect; value expressions such as helpfulness, friendship, empathy; and with the house, family, home metaphors. It has also been understood that some of the students (13%) have a negative perception of school, they do not like school, and they continue to school because it is compulsory. It was among the findings of the research that the students with a negative perception of school have described school by metaphors expressing physical and emotional discomfort such as boredom, suffering, headache, burnout; and metaphors emphasizing the restriction of freedom such as prison, captivity, and watch tower. In addition, it has been determined that students with negative perceptions have individual and organizational reasons for these perceptions. In the research, it was concluded that there are common meanings in students’ perceptions of school in different countries towards the school, and no matter what language they speak, the students describe the school with similar thoughts and feelings. In this direction, suggestions have been made to increase the awareness of executives and policymakers about students' perceptions of school, to consider the interests and needs of students in the physical design of schools, to implement support programs that will enable students to develop a positive perception of the school, and to conduct longitudinal studies examining the reasons for these perceptions of students with negative perceptions.